Libyan Agriculture: A Review of Past Efforts, Current Challenges and Future Prospects - Abagandura, Gandura O; Park, Dara (Journal of Natural Sciences Research, 2016)
By increasing the agricultural sector productivity, Libya will decrease their current dependency on other countries for food and potentially could stimulate the economy by increasing food exports. Like many other countries in the region, agriculture in Libya is constrained by its limited arable land and low soil fertility. Desertification and limited freshwater resources are the two greatest challenges for future agricultural development. In addition, the intrusion of the seawater into the groundwater is causing soils to become saltaffected. Many important crops in the country are susceptible to pests. These challenges have not been addressed because of the lack of specialists and institutions engaged in the National Plant Protection Program. Increasing crop productivity depends on identifying proper management strategies of natural resources and pests as well as seed development.
Keywords: Agriculture -- Djebel Nefousa